Varieties of pure first-order logics of partial quasiary predicates - Шкільняк, Степан (Київський національний університет імені Тараса Шевченка, 2024)
Classical predicate logic typically lies at the basis of various logical systems successfully used in computer science and programming. However, classical logic has fundamental limitations that complicate its application. Therefore, the task of developing new, program-oriented logics becomes important; this highlights the relevance of the proposed research. In this work we study new program-oriented logical formalisms – pure first-order composition-nominative logics of partial quasiary predicates, PCNL. Depending on the presence and type of special predicates-indicators, and equality predicates (weak or strong), the use of traditional or extended renomination, in this paper we specify a number of classes of PCNL. Special predicates-indicators determine the presence of components with the corresponding subject name in the input data, which is necessary to consider for the quantifier elimination in the logics of non-monotonic predicates. Two types of these predicates can be distinguished: total, which determine the presence or absence of a component with a given name, and partial, which only detect the presence of such a component. We propose partial predicates-indicators and the corresponding classes of PCNL. The basic compositions of these logics are described, and their properties are presented. The languages of the introduced classes of logics are specified, and a number of logical consequence relations for these languages are defined. The characteristics of these relations are investigated, and the relationships between them are provided. Pages of the article in the issue: 80 - 88 Language of the article: English

В основі різноманітних логічних систем, які успішно використовуються в інформатиці й програмуванні,зазвичай лежить класична логіка предикатів. Проте класична логіка має принципові обмеження, що ускладнює її застосування. Тому на перший план виходить задача побудови нових, програмно-орієнтованих логік. Це засвідчує актуальність пропонованого дослідження. В цій роботі досліджуються нові програмно-орієнтовані логічні формалізми  – чисті першопорядкові композиційно-номінативні логіки часткових квазіарних предикатів, такі логіки названо PCNL.  Залежно від наявності й різновиду спеціальних предикатів-індикаторів, від наявності й різновиду предикатів рівності (слабкої чи строгої) та від використання традиційної чи розширеної реномінації, в роботі виділено низку різновидів PCNL. Спеціальні предикати-індикатори визначають наявність у вхідних даних компонент з відповідним предметниміменем, враховувати таку наявність необхідно для елімінації кванторів у логіках немонотонних предикатів.Виділено два різновиди предикатів-індикаторів: тотальні, які визначають наявність чи відсутність компоненти з певним іменем, та часткові, які визначають лише наявність такої компоненти. В цій роботі ми пропонуємо часткові предикати-індикатори та відповідні класи PCNL. Описано базові композиції таких логік, наведено властивості цих композицій. Описано мови виділених класів логік, визначено низку відношень логічного наслідку в цих мовах. Розглянуто особливості цих відношень, наведено співвідношення між ними.
Різновиди чистих першопорядкових логік часткових квазіарних предикатів
Keywords: логіка; частковий предикат; рівність; логічний наслідок; logic; partial predicate; equality; logical consequence